N Terminal-Pro Brain Natriuretic Peptide (Nt–ProBNP) Pada Penderita Hipertensi Derajat 1 Dan Derajat 2 - Supriati Wila Djami; Mansyur Arif; Uleng Bahrun (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2019)
The level of N Terminal – Pro Brain Natriuretic Peptide was independently associated with an increased risk of hypertension. This study aimed to determine the difference of NT-proBNP serum levels and the correlation between the levels of NT-proBNP in patients with hypertension stage 1 and stage 2. This research was conducted at RSUP dr. Wahidin Sudirohusodo in August -September 2018. The research was conducted at Dr. Wahidin Sudirohusodo RSUP from August through September 2018. The study used a cross-sectional design with a total of 72 hypertensive patients, who had met the inclusive criteria. NT-proBNP levels were measured using the ELISA (Enzyme-Linked Immunosorbent Assay) method. The collected data is processed using Mann Whitney Different Test and Spearman's rho Correlation Test. The study results indicated that the level of NT-proBNP in the hypertensive patients with stage 2 (172.85 + 316.26) was higher and significantly different (p = <0.001) compared to hypertensive patients stage 1 (34.98 + 28.99). NT-proBNP levels were higher in the hypertensive group of >6 years (247.83+361.01) than in the hypertensive group <6 years (62.79+164.66), statistically there were significant differences between the two groups (p=0.010). There was in a significant correlation between the levels of NT-proBNP in hypertensive patients, stage 1 and stage 2 (p = 0.862) even though it showed significantly different results.